Apoyo a proyectos de infraestructura para mejorar las metodologías usadas por el municipio de Sogamoso – Boyacá (2023)
In this document, the civil engineering student shows his contribution as an intern at the infrastructure secretariat. His academic training and experience in the field of civil engineering provides him with the necessary technical knowledge to understand infrastructure projects and participate in their development, collaborating in the review and analysis of proposed infrastructure projects, contributing his knowledge in technical and of viability. Also supporting the supervision and control of the execution of the works, ensuring that the established quality and safety standards are met, contributing to the review of balances and budget, guaranteeing efficient use of available resources. Likewise, participating in the preparation of reports and technical documents, providing expertise in the writing and presentation of relevant information. In summary, the civil engineering student, as an intern in the infrastructure secretariat, contributed significantly to the processes carried out in said secretariat. Their collaboration contributed to a more efficient and effective operation in the rehabilitation of project of the Infrastructure Secretariat.